2007
DOI: 10.1111/j.1442-9071.2007.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐penetrating glaucoma surgery augmented with mitomycin C or 5‐fluorouracil in eyes at high risk of failure of filtration surgery: long‐term results

Abstract: NPGS augmented with small-volume MMC/5FU provides good long-term IOP control in eyes at high risk of failure with a lower incidence of complications compared with augmented trabeculectomy and eliminates the need for postoperative bleb or suture manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Other studies evaluating the use of adjunctive MMC with other nonfiltering glaucoma surgeries support the findings of the study reported here. 17 This case series adds to our understanding of factors, which may help to improve the success of canaloplasty. The use of MMC apparently contributed to further reductions in IOP and medication use, conceivably slowing the inflammatory response in the scleral lake and TDW.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies evaluating the use of adjunctive MMC with other nonfiltering glaucoma surgeries support the findings of the study reported here. 17 This case series adds to our understanding of factors, which may help to improve the success of canaloplasty. The use of MMC apparently contributed to further reductions in IOP and medication use, conceivably slowing the inflammatory response in the scleral lake and TDW.…”
Section: Discussionmentioning
confidence: 92%
“…16 Intraoperative MMC is thought to prevent collapse of the intrascleral lake and increase the success rate of viscocanalostomy particularly in complicated eyes and without a substantial increase in the risk of hypotony and endophthalmitis. 17 As IOP control in canaloplasty may also be dependent on the formation of a scleral lake in addition to viscodilation and trabecular meshwork tensioning, low-dose intraoperative MMC could have a beneficial effect on canaloplasty, especially in high-risk patients. In this retrospective study, the use of low-dose MMC adjuvant therapy in conjunction with canaloplasty was investigated in a preliminary, noncomparative case series.…”
mentioning
confidence: 99%
“…Non-penetrating glaucoma surgery (NPGS) has been shown to provide comparable long-term qualified success rates to trabeculectomy, with reduced post-operative complications [911] but there is limited information on its success in patients with advanced glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…25 DS with MMC has been reported to be a safe and effective procedure for eyes with failed trabeculectomy. 26,27 There has been a lack of consensus among glaucoma surgeons as to the best surgical option in eyes at a high-risk-to-failure, such as previous intraocular surgery. The Tube versus Trabeculectomy (TVT) trial was designed to prospectively assess trabeculectomy and Bearveldt tube implant (BGI) surgery, both augmented with MMC, in eyes with previous cataract surgery and/or failed trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%